Revitalisasi Perancangan Interior Sanggar Tari Tradisional di Surabaya - Tansir, Silas Mitchell Enrico (Intra, 2015)
Indonesia is a rich country in culture and race. With so many regional culture of the Indonesian nation, it certainly needs to be preserved and were well developed specifically to keep known and not consumed by age. A very diverse culture that one of them is the traditional dance. The development of traditional dance of life at this time showed a very alarming symptom. This setback was rated by experts because the dance tradition of guidance andÂ  dance that seems slow. This setback also due to the lack of adequate facilities to be used as a means of learning dance formally. Existing facilities in a traditional dance studio in several cities in Indonesia are still not able to answer the needs of space. This is related in some problems, such as the need for any space required in a traditional dance studio and how the amount of space sufficient to accommodate any activity contained in the dance studio. In addition, the interior design of the traditional dance studio in East Java is still not able to raise their own cultural elements. As the next generation, is expected to be able to maintain and preserve the culture. This design is done to promote the development of traditional dance studio in Surabaya associated with reduced public interest Indonesian original culture. Highlights in this design is focused on the problem of how to design interestingly adn functionally a traditional danc, so studio is able to attract the public interest so as to deepen and preserve the culture - the culture contained in the Indonesian nation.